Towards a definition of excellence in sport coaching - Côté, J.; Young, B.; North, J.; Duffy, P. (International Journal of Coaching Science, 2007)
In this paper, we propose different definitions of coaching excellence based on two principles. First, the application of coaching skill, as in any other domain of excellence, is context-dependent. Second, excellent coaches are knowledgeable and constantly assemble mental models that enable them to meet their athletes` needs and to effectively manage the central duties of coaching - organization, training, and competition. Four categories of coaches and corresponding definitions are proposed based on the characteristics of athletes and the developmentally-appropriate sport contexts: 1) participation coaches for children, 2) participation coaches for teens and adults, 3) performance coaches for young adolescents, 4) performance coaches for older adolescents and adults.